Environmental effects of thermal barrier coating with waste cooking palm oil methyl ester blends in a diesel engine. Issue 2 (4th March 2019) - Karthickeyan, V.; Balamurugan, P.; Senthil, R.
ABSTRACT: Waste cooking oil was selected as the source material for the development of an alternative fuel. The conversion of waste cooking palm oil (WCO) into waste cooking palm oil methyl ester (WCOME) was carried out through a transesterification process. The chemical components and composition of the prepared neat methyl ester was investigated using Fourier Transform Infrared spectroscopy (FTIR) and Gas Chromatography Mass Spectrometry (GC-MS) analyses. Physio-chemical properties were determined based on ASTM standards. A thermal barrier coating was applied to the engine combustion chamber using an air plasma spray technique to reduce exhaust emission. A Kirloskar TV1 model single-cylinder direct injection diesel engine with high precision eddy current dynamometer was used for experimentation. Low brake thermal efficiency and high brake specific fuel consumption was observed for 20WCOME in the coated engine. Low CO, HC and smoke emissions were observed for 10WCOME and 20WCOME with an increase in NOx emission. Abstract : Highlights Waste cooking palm oil methyl ester (WCOME) in a partially stabilized zirconia (PSZ) coated engine was attempted. The chemical properties of WCOME using FTIR and GC-MS were identified and recorded. A plasma spray coating technique was used to coat some combustion chamber components (piston head, cylinder head and intake and exhaust valve). The coated engine showed low brake thermal efficiency and high brake specific fuel consumption for WCOME blends. The coated engine with WCOME blends exhibited low emissions of CO, HC and smoke with an increase in NOx emissions.